Bathymetry, Electromagnetic Streamlines and the Marine Controlled Source Electromagnetic Method - Pethick, Andrew; Harris, Brett (CSIRO Publishing, 2014)
Seafloor topography must influence the strength and direction of electromagnetic fields generated during deep ocean controlled source electromagnetic surveying. Neither mathematical equation nor rules of thumb provide a clear perspective of how changes in water column thickness alters electromagnetic fields that engulf hundreds of cubic kilometres of air, ocean, host and reservoir. We use streamline visualisation to provide a generalised representation of how electromagnetic fields propagate into a 2D geo-electrical setting that includes strong bathymetry. Of particular interest are; (i) 'dead zones' where electric fields at the ocean floor are demonstrated to be weak and (ii) the 'airwave' that appears in the electric field streamlines as circulating vortices with a shape that is clearly influenced by changes in ocean depth. Our analysis of the distribution of electric fields for deep and shallow water examples, alludes to potential benefits from placement of receivers and or transmitters higher in the water column as is the case for towed receiver geometries. Real time streamline representation probably holds the most value at the survey planning stage especially for shallow water marine EM surveys where ocean bottom topography is likely to be consequential.